ANALISIS PENGELOLAAN KEUANGAN DAERAH TERHADAP PRODUK DOMESTIK REGIONAL BRUTO (PDRB) DI KABUPATEN/KOTA PROVINSI KALIMANTAN SELATAN - Syarifah Aisza Faradiba Alfi; Ida Nuraini (Jurnal Ilmu Ekonomi JIE, 2018)
This study aims to determine how big the management of regional financial to Gross Regional Domestic Product (GRDP) in the District / City of South Kalimantan Province in 2012-2016. The research of variables that used are (1) the ratio of local financial independence, (2) the effectiveness ratio of PAD and (3) capital expenditure. The population in this study were 13 districts / municipalities in South Kalimantan Province and samples were taken by purposive sampling that is all population used as sample. Analyzer used is multiple linear regression analysis. The results of this study indicate that the management of regional finance has a significant effect on the Gross Regional Domestic Product (GRDP). Based on the results of multiple linear regression test, it is known that the regional financial independence has a significant positive effect to the Gross Regional Domestic Product (GRDP), the effectiveness of PAD has a significant positive effect on Gross Regional Domestic Product (GRDP), and capital expenditure has a significant positive effect on Gross Regional Domestic Product (GRDP).Keywords: Regional Financial Management, Regional Financial Independence, PAD Effectiveness, Capital Expenditure, Gross Regional Domestic Product.